Reversible expansion of gallium-stabilized δ-plutonium - Wolfer, W.G.; Oudot, B.; Baclet, N. (Journal of nuclear materials, 2006)
It is shown that the transient expansion of plutonium–gallium alloys observed both in the lattice parameter as well as in the dimension of a sample held at ambient temperature can be explained by assuming incipient precipitation of Pu 3Ga. However, this ordered ζ′-phase is also subject to radiation-induced disordering. As a result, the gallium-stabilized δ-phase, being metastable at ambient temperature, is driven towards thermodynamic equilibrium by radiation-enhanced diffusion of gallium and at the same time reverted back to its metastable state by radiation-induced disordering. A steady state is reached in which only a modest fraction of the gallium present is arranged in ordered ζ′-phase regions.